EDUKASI KESEHATAN WANITA: PENINGKATAN PENGETAHUAN SISWI TENTANG RISIKO STRES DAN YOGA SEBAGAI METODE MANAJEMEN STRES - Pratiwi, Dilia Ananda; Marlina, Lina; Iskandar, Hauzan Yazid Nabil; Nurawaliah, Alfiyah Siti; Sari, Nesta (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
One factor that contributes to the pathogenesis of almost all diseases, including PCOS, is stress. A study shows that one of the health needs required especially by adolescent girls is psycho-emotional services. In West Java Province, there are approximately one million high school and equivalent students in the 2022/2023 academic year. Of this number it includes students who pursue their upper secondary education in Sindangmulya District, such as SMK Bintang Harapan. Like high school students in general, students in these schools are vulnerable to stress stemming from the academic demands given by schools in the form of assignments with limited time. Among the recommended stress management techniques, some involve physical exercises, such as yoga. Based on this, education related to yoga as a stress management method needs to be implemented. The results obtained after this activity were an increase in the knowledge of female students regarding the implications of yoga for stress management, with a 79.3% increase in the percentage of students who achieved a perfect score, averaging 10.00.